Populist Rhetorics
XI, 247 p. 3 illus., 2 illus. in color.
Keywords: This book proposes a unified approach to populism that sees it as a primarily rhetorical concept. Populism is on the rise worldwide with both populist leaders and movements gaining power, and the term “populism” resounds in political debate, journalism, and scholarship. Populism as a phenomenon seems to instantiate perennial issues besetting rhetoric (e.g., the charges of manipulation, exclusive reliance on opinion over knowledge, and abuse of emotional appeals), yet relatively little research on populism has emerged from the discipline of rhetoric. This volume investigates the theory and practice of populism under the heading of rhetoric but as an interdisciplinary effort involving scholars in rhetoric as well as neighbouring disciplines such as political science and sociology. Seven case studies covering Germany, Greece, Hungary, Italy, UK, USA, and Venezuela offer conceptual discussions as well as close analyses applying both historical and theoretical approaches. In the introduction, the editors outline the problem of populism and their project, presenting the book’s wide-spanning case-based explorations. In an afterword they seek to distil a “minimal” rhetorical definition of populism. The claim or pretense to speak for “the people” emerges as the feature that connects the highly diverse instances studied in the book—and populisms in general, the editors hypothesize. They argue that this prevalent rhetorical move, often glossed over as unremarkable and banal, is in principle more debatable and deserving of more vigilant scrutiny than usually assumed. Christian Kock is Emeritus Professor of Rhetoric at the University of Copenhagen, Denmark. He has published in Philosophy and Rhetoric, Argumentation, Political Communication, Rhetorica, Rhetorica Scandinavica, Paradigmi, Informal Logic, Controversia and many other journals and has authored and edited several books in Danish and English on political rhetoric, argumentation, and public debate, most recently his Deliberative Rhetoric: Arguing about Doing (2017). Lisa Villadsen is Professor and Head of the Section of Rhetoric at the University of Copenhagen, Denmark. She has published in Rhetoric Society Quarterly, Quarterly Journal of Speech, Javnost, Rhetorica Scandinavica, and other journals on official apologies, political rhetoric, dissent, and populism, most recently “Low Style the High Way: Rhetorical Mainstreaming of Populism” in the edited volume Vox Populi: Populism as a Rhetorical and Democratic Challenge (2020).